22 Players Run After the Ball for 90 Minutes, and in the End England Wins. German Views of the 1935 and 1938 Germany–England Football Matches - Vares, Vesa (Taylor & Francis, 2025)
This article studies the politico-diplomatic dimension of the 1935 and 1938 Germany-England football matches played during the National Socialist era. Despite being represented in both countries as international friendlies, these games proved highly politicized affairs because of the centrality of the British-German relationship in international affairs and the politization and diplomatization of international sport during the 1930s. The 1935 game, played in London, became the focus for a high-profile public campaign, led by trade union, Jewish, and other lobbying groups hostile to Nazi Germany, to ban the match. In turn, the 1938 fixture is famed for the Nazi salute, the ‘infamous gesture’ that British diplomats and Football Association officials instructed the England team to give before the beginning of the match. Using the archives of the Auswärtiges Amt (Foreign Ministry) and Bundesarchiv (Federal Archives) as well as a selection of German newspapers, this article provides an informed German perspective on both matches, which hitherto have been studied principally from a British perspective. Focused upon German aims, perceptions, political influences, and propaganda goals, this case study highlights the ‘soft power’ methods of totalitarianism in terms of both the adaptation of totalitarianism to football and the adaptation of football to totalitarianism.